PENYELESAIAN SENGKETA PERJANJIAN NOMINEE TENTANG PERALIHAN HAK MILIK ATAS TANAH KEPADA WARGA NEGARA ASING (WNA) DITINJAU DARI PASAL 26 AYAT (2) UUPA - Ni Putu Tanjung Eka Wijayani (Jurnal Aktual Justice, 2018)
The nominee agreement is an agreement made between a person who by law can not be the subject of a particular land title (in this case the Right or the Right to Build). In this case a foreign national with an Indonesian citizen, which is intended for foreigners to possess the land of ownership or the right to use the building (de facto), but legally (de jure) of the land concerned on behalf of the Indonesian citizen. In other words, Indonesian citizen borrowed its name by foreigners citizen (acting as nominee). The existence of the obscurity of the norm in Article 26 paragraph (2) concerning whether the legal act of a foreigner / foreigner in a notarial deed called a nominee deed is valid for one year and thereafter if not transferred shall fall to the state having the same meaning and intent with the provision of Article 21 paragraph (3). This is particularly important to be considered since Article 26 paragraph (2) implicitly prohibits that legal acts directly or indirectly intended to transfer land rights from Indonesian citizens to foreigners / foreigners are null and void because the law and land fall to the State . Because the phrase that states other acts intended to directly or indirectly transfer the ownership rights to a stranger in Article 26 paragraph (2) of the BAL raises various interpretations (interpretations) so that there arises doubts that lead to the escape of norms (vague van normen).